High-nickel ternary positive electrode material of lithium ion battery as well as preparation method and application of high-nickel ternary positive electrode material
By introducing thermal shock treatment technology into high-nickel ternary positive electrode materials, the structural damage and cycle stability problems of the material in a charged state are solved, and the element concentration gradient is maintained, achieving high capacity and high cycle stability effects. Suitable for industrial production.
Patent Information
- Application Number
- CN202411615225.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-13
Smart Images

Figure CN119219077A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy, in particular to a lithium-ion battery high-nickel ternary positive electrode material for a lithium-ion power battery and its preparation method and application Background Art
[0002] With the continuous development of new energy vehicles, the market has higher and higher requirements for the energy density, cycle life and safety of lithium-ion power batteries. In recent years, nickel-cobalt-manganese / aluminum ternary positive electrode materials have been developed and applied to a certain extent due to their relatively low cost, high specific capacity / energy and low toxicity. Therefore, high-nickel ternary positive electrode materials are used commercially on a large scale. With the increase of nickel content in ternary materials, the specific capacity gradually increases, but at the same time, various properties such as material cycle stability are significantly reduced. How to ensure that high-nickel positive electrode materials have high capacity and excellent cycle stability has always been the focus of research in the industry.
[0003] One of the main reasons for the poor stability of high-nickel ternary cathode materials is that when the battery is charged, the highly reactive Ni 4+ It is easy to produce side reactions with the electrolyte solution, causing structural damage to the material, while releasing a large amount of oxygen and heat, thereby reducing the thermal stability and safety performance of the battery. Secondly, the mutual migration of transition metal ions and lithium ions and the corrosion of the electrolyte solution during the charging / discharging process cause the surface of the primary particles to become rough, the initial layered structure is destroyed, and the surface is destroyed, eventually transforming into a completely disordered and inactive NiO rock salt phase.
[0004] The full concentration gradient structure design of the material can minimize the nickel content on the surface and reduce the Ni 4+The high reactivity of the electrolyte reduces the corrosion of the material matrix and the occurrence of side reactions. In the full concentration gradient material, the nickel content in the core of the secondary particles is high within the entire particle range, providing a higher capacity. It shows a gradual downward trend from the core to the particle surface, and the concentration of the elements is a gradual process, so the material has good compatibility and a more stable surface, so the cycle performance is better. Concentration gradient materials are very likely to be used on a large scale in the future. China Guolian Automotive Power Battery Research Institute Co., Ltd. (application publication number CN111092221A) discloses a method for preparing a high-nickel ternary material with a transition metal element concentration gradient and the prepared material. Through a multi-stage roasting method, a long time in a low-temperature stage is combined with a short time in a high-temperature stage, thereby suppressing the abnormal growth of primary particles and the mutual diffusion of transition metals in the current gradient precursor during the roasting process after lithium addition. The resulting performance is improved to a certain extent. South Korea's ECOPRO BM Company (application publication number CN107112516A) disclosed a method for preparing a positive electrode active material for lithium secondary batteries that exhibits a concentration gradient, which utilizes the formed barrier layer to maintain the concentration gradient layer when heat diffusion is generated during the subsequent heat treatment process, thereby presenting a positive electrode active material with a concentration gradient. The above methods all start from the precursor preparation process and control the roasting process to inhibit the interdiffusion of transition metal element concentration gradients.
[0005] However, the industrialization of concentration gradient materials still faces many problems, the most important of which is the problem of maintaining the element concentration gradient. During the long-term roasting process in the traditional furnace, ion diffusion homogenization is inevitable, resulting in a decrease in the element concentration gradient. The final prepared positive electrode material cannot strictly meet the trend of continuous element concentration gradient distribution and has poor performance. Summary of the invention
[0006] The present invention aims to solve the problem of poor stability of positive electrode materials in the prior art. By rationally configuring the precursor composition and introducing thermal shock, the problem of disappearance of element concentration gradient caused by homogenization of ion diffusion in the synthesized concentration gradient precursor during the roasting process is overcome, and a high-nickel ternary positive electrode material with a trend of continuous element concentration gradient distribution is obtained, showing the advantages of high capacity and high cycle stability.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a high-nickel ternary positive electrode material for a lithium-ion battery, the method comprising: preparing a precursor Ni having an element concentration gradient structure x Co y M 1-x-y (OH)2 and lithium hydroxide are mixed, and the mixed powder is subjected to thermal shock treatment using Joule heat to obtain a high-performance high-nickel ternary positive electrode material with element gradient distribution; Ni x Co y M1-x-y (OH)2, 0.7≤x<1.0, 0.01≤y<0.1; M is Mn, Al, W, Nb, Mo, Ta or Zr; the concentration of nickel decreases gradually from the core to the particle surface; lithium hydroxide and Ni x Co y M 1-x-y The total molar ratio of metal ions in (OH)2 is 1.0-1.2:1; the thermal shock treatment is carried out in a pure oxygen atmosphere, the heating and cooling rate is 373 K / s-773K / s, the target temperature is 700℃-900℃, and the holding time is 120s-360s.
[0008] The precursor Ni with element concentration gradient structure of the present invention x Co y M 1-x-y (OH)2 is prepared in one step by a co-precipitation method, including but not limited to the preparation methods of the precursors disclosed in the aforementioned CN111092221A and CN107112516A.
[0009] In certain embodiments of the present invention, the mixed powder is spread on a heated substrate, and the heated substrate is electrified in an air atmosphere to achieve thermal shock treatment of the powder.
[0010] In certain embodiments of the present invention, the heating substrate used is carbon cloth, graphite paper, or metal foil.
[0011] The present invention also relates to a positive electrode material prepared by the above method, wherein the positive electrode material is a high-nickel ternary positive electrode material having an α-NaFeO2 layered material and belonging to R m space group, the secondary particles of the positive electrode material are spherical, with an average particle size of 6-13 μm and a tap density of 1.8-2.7 g / cm 3 .
[0012] The present invention also relates to the application of the above positive electrode material in lithium ion power batteries.
[0013] The positive electrode material formed by sintering of the present invention has an obvious internal concentration gradient trend, high tap density, high capacity, stable cycle performance, can well meet the requirements of power batteries for high energy density, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The high nickel ternary precursor Ni with a concentration gradient structure prepared in Example 1 0.8 Co 0.15 Al 0.05 Radial distribution of Ni, Co and Al element contents in the cross section of (OH)2 secondary particles.
[0015] Figure 2 The high nickel ternary positive electrode material Ni with a concentration gradient structure prepared in Example 1 0.8 Co 0.15 Al 0.05 Radial distribution of Ni, Co and Al element contents in the cross section of O2 secondary particles.
[0016] Figure 3 The high nickel ternary positive electrode material Ni prepared in Example 1 0.8 Co 0.15 Al 0.05 XRD pattern of O2.
[0017] Figure 4 The high nickel ternary precursor Ni prepared in Example 1 0.8 Co 0.15 Al 0.05 (OH)2 and positive electrode material Ni 0.8 Co 0.15 Al 0.05 Electron microscopic image of O2.
[0018] Figure 5 The high nickel ternary positive electrode material Ni with a concentration gradient structure prepared in Example 1 0.8 Co 0.15 Al 0.05 O2 first charge and discharge curve and cycle performance curve.
[0019] Figure 6 The high nickel ternary precursor Ni with a concentration gradient structure prepared in Example 2 0.8 Co 0.15 Al 0.05 Radial distribution of Ni, Co and Al element contents in the cross section of (OH)2 secondary particles.
[0020] Figure 7 The high nickel ternary positive electrode material Ni with a concentration gradient structure prepared in Example 2 0.8 Co 0.15 Al 0.05 Radial distribution of Ni, Co and Al element contents in the cross section of O2 secondary particles.
[0021] Figure 8 The high nickel ternary positive electrode material Ni prepared in Example 2 0.8 Co 0.15 Al 0.05 XRD pattern of O2.
[0022] Fig. 9 The high nickel ternary precursor Ni prepared in Example 2 0.8 Co 0.15 Al 0.05(OH)2 and positive electrode material Ni 0.8 Co 0.15 Al 0.05 Electron microscopic image of O2.
[0023] Fig.10 The high nickel ternary positive electrode material Ni with a concentration gradient structure prepared in Example 2 0.8 Co 0.15 Al 0.05 O2 first charge and discharge curve and cycle performance curve.
[0024] Fig.11 The high nickel ternary positive electrode material Ni with a concentration gradient structure prepared in Example 3 0.8 Co 0.15 Al 0.05 Radial distribution of Ni, Co and Al element contents in the cross section of O2 secondary particles.
[0025] Fig.12 The high nickel ternary positive electrode material Ni with a concentration gradient structure prepared in Comparative Example 1 0.8 Co 0.15 Al 0.05 Radial distribution of Ni, Co and Al element contents in the cross section of O2 secondary particles.
[0026] Fig.13 The high nickel ternary positive electrode material Ni prepared in comparative example 1 0.8 Co 0.15 Al 0.05 O2 first charge and discharge curve and cycle performance curve.
[0027] Fig.14 This is the radial distribution of the element content of the high-nickel ternary positive electrode material prepared in Example 2.
[0028] Fig.15 These are the first charge and discharge curves and cycle performance curves of Comparative Example 2. DETAILED DESCRIPTION
[0029] The present invention optimizes the parameters of the rapid Joule heating process after the high-nickel ternary precursor with a concentration gradient structure is mixed with lithium hydroxide, achieving the purpose of suppressing the diffusion of transition metal ions in the concentration gradient precursor during long-term roasting, and avoiding the problem of disappearance of element concentration gradient caused by traditional furnace roasting. The concentration gradient distribution of elements in the high-nickel ternary positive electrode material is retained to the greatest extent, inheriting the concentration gradient distribution of the high-nickel ternary precursor. The preparation of a high-nickel ternary positive electrode material with high capacity and high cycle stability is achieved.
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions and advantages of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0032] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0033] In the following examples, a high nickel ternary precursor Ni with a concentration gradient structure is used. 0.8 Co 0.15 Al 0.05 (OH)2 is used as a sample to illustrate the present invention so that those skilled in the art can fully understand the implementation scheme and technical effects of the present invention. Those skilled in the art should understand that other high nickel ternary precursors Ni with a concentration gradient structure obtained by coprecipitation method x Co y M 1-x-y (OH)2 (0.7≤x<1.0, 0.01≤y<0.1; M is Mn, Al, W, Nb, Mo, Ta or Zr) is also applicable to the present invention. 0.8 Co 0.15 Al 0.05 (OH)2 is only for the purpose of describing specific embodiments and is not intended to limit the present application.
[0034] Example 1 Step 1: Prepare a mixture by mixing lithium hydroxide with a concentration gradient precursor Ni 0.8 Co 0.15 Al 0.05 (OH)2 was mixed in a total molar ratio of 1.03:1 and put into a ball mill and stirred evenly to obtain a mixed material; Ni 0.8 Co 0.15 Al 0.05 The core component of (OH)2 is designed to be Ni 0.95 Al 0.05 (OH)2, the surface component is designed to be Ni 0.55 Co 0.4 ACol 0.05(OH)2, by adjusting the feed rate of various salt solutions using the co-precipitation method, the nickel element concentration gradient from the core to the surface of the high-nickel precursor secondary particles showed a gradual downward trend, the cobalt element concentration gradient showed a gradual upward trend, and the aluminum element concentration gradient trend remained unchanged. Figure 1 The radial distribution of Ni, Co and Al element contents in the cross section of high-nickel ternary precursor particles with a concentration gradient structure prepared by the co-precipitation method is demonstrated.
[0035] Step 2: The mixture obtained above was calcined by a rapid Joule heating process. The sample was heated at an ultra-fast heating rate of 673 K / s in an oxygen atmosphere, and the holding time at 800 ° C was 210 s. The cooling rate was measured to be 673 K / s when the temperature was naturally cooled to obtain a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2.
[0036] The concentration gradient distribution of the elements in the prepared high-nickel ternary cathode material is retained to the greatest extent, inheriting the concentration gradient distribution of the high-nickel ternary precursor, such as Figure 2 , and has a typical α-NaFeO2 layered material, belonging to R m space group (such as Figure 3 ), the secondary particles of the positive electrode material are spherical or quasi-spherical (such as Figure 4 ), with an average particle size of 12 μm and a tap density of 2.3 g / cm 3 The button half-cell was made for electrochemical performance testing. The constant current and constant voltage charging and constant current discharge cut-off voltage were 2.8-4.3 V. The 0.1C first discharge capacity was 200 mAh / g. The capacity retention rate after 100 cycles at 1C was 90.4%. Figure 5 .
[0037] Example 2 Step 1: Prepare a mixture by mixing lithium hydroxide with a concentration gradient precursor Ni 0.8 Co 0.15 Al 0.05 (OH)2 is mixed in a total molar ratio of 1:1 and put into a ball mill and stirred evenly to obtain a mixed material; Ni 0.8 Co 0.15 Al 0.05 The core component of (OH)2 is designed to be Ni 0.85 Co 0.15 (OH)2, the surface component is designed to be Ni 0.75 Co 0.15 ACol 0.1(OH)2, by adjusting the feed rate of various salt solutions using the co-precipitation method, the nickel element concentration gradient from the core to the surface of the high-nickel precursor secondary particles showed a gradual downward trend, the aluminum element concentration gradient showed a gradual upward trend, and the cobalt element concentration gradient trend remained unchanged. Figure 6 The radial distribution of Ni, Co and Al element contents in the cross section of high-nickel ternary precursor particles with a concentration gradient structure prepared by the co-precipitation method is demonstrated.
[0038] Step 2: The mixture obtained above was calcined by a rapid Joule heating process. The sample was heated at an ultra-fast heating rate of 673 K / s in an oxygen atmosphere, and the holding time at 700 ° C was 360 s. The cooling rate was measured at 373 K / s when the temperature was naturally cooled to obtain a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2.
[0039] The concentration gradient distribution of the elements in the prepared high-nickel ternary cathode material is retained to the greatest extent, inheriting the concentration gradient distribution of the high-nickel ternary precursor, such as Figure 7 , and has a typical α-NaFeO2 layered material, belonging to R m space group (such as Figure 8 ), the secondary particles of the positive electrode material are spherical or quasi-spherical (such as Fig. 9 ), with an average particle size of 11 μm and a tap density of 2.35 g / cm 3 The button half-cell was made for electrochemical performance testing. The constant current and constant voltage charging and constant current discharge cut-off voltage were 2.8-4.3 V. The 0.1C first discharge capacity was 200 mAh / g. The capacity retention rate after 100 cycles at 1C was 93%. Fig.10 .
[0040] Example 3 This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is the same as that of Embodiment 1 except that the holding time at 900°C in the rapid Joule heating process described in step 2 is 120s and the natural cooling rate is measured to be 773K / s.
[0041] The concentration gradient distribution of elements in the prepared high-nickel ternary cathode material is retained to the greatest extent, such as Fig.11 ,By prolonging the holding time of rapid Joule heating, the concentration gradient distribution trend of the elements did not change, and it inherited the concentration gradient distribution trend of the high-nickel ternary precursor.
[0042] Comparative Example 1 Step 1: Prepare a mixture by mixing lithium hydroxide with a concentration gradient precursor Ni 0.8 Co 0.15 Al0.05 (OH)2 was mixed in a total molar ratio of 1.2:1 and put into a ball mill to stir evenly to obtain a mixed material; the concentration gradient precursor Ni 0.8 Co 0.15 Al 0.05 (OH)2 is the same as in Example 1.
[0043] Step 2: The mixture obtained above was calcined in a conventional tube furnace, heated at a heating rate of 2°C / min in an oxygen atmosphere, kept at 800°C for 12h, and then slowly cooled to obtain the high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2.
[0044] Without any treatment, the concentration gradient trend of Ni and Co elements in the prepared high-nickel ternary cathode material particles slowed down significantly and almost disappeared. Fig.12 The button half-cell was made for electrochemical performance testing. The constant current and constant voltage charging and constant current discharge cut-off voltage were 2.8-4.3 V. The 0.1C first discharge capacity was 193 mAh / g. The capacity retention rate after 100 cycles at 0.5C was 75%. Fig.13 .
[0045] Fig.12 The paper shows that a mixture of a high-nickel ternary precursor and lithium with a concentration gradient structure is calcined for a long time in a traditional tube furnace. During the long-term high-temperature insulation process, the concentration gradient of nickel and cobalt elements gradually slows down until it disappears. At the same time, Fig.13 The corresponding electrochemical performance is shown. The disappearance of the concentration gradient does not bring about a change in the initial capacity, but affects the cycle stability of the material. The nickel content on its surface returns to the previous high nickel content composition. The highly reactive Ni 4+ It also produces side reactions with the electrolyte solution, causing structural damage to the material, thereby reducing the cycle stability. The slowing down or disappearance of the concentration gradient trend is a challenge currently faced by high-concentration-gradient nickel ternary materials in the preparation process.
[0046] Comparative Example 2 Step 1: Prepare a mixture by mixing lithium hydroxide with a concentration gradient precursor Ni 0.8 Co 0.15 Al 0.05 (OH)2 was mixed in a total molar ratio of 1.03:1 and put into a ball mill to stir evenly to obtain a mixed material; the concentration gradient precursor Ni 0.8 Co 0.15 Al 0.05 (OH)2 is the same as in Example 1.
[0047] Step 2: The mixture obtained above is calcined in a conventional tube furnace in multiple stages, and the temperature is increased at a heating rate of 2°C / min in an oxygen atmosphere, 450°C → 650°C → 780°C → 500°C → room temperature, and then slowly cooled to obtain the high-nickel ternary positive electrode material LiNi 0.8 Co 0.15 Al 0.05 O2.
[0048] The prepared high-nickel ternary cathode material is calcined by a multi-stage calcination method, and the concentration gradient trend of Ni and Co elements in the particles is still significantly slowed down, such as Fig.14 The button half-cell was made for electrochemical performance testing. The constant current and constant voltage charging and constant current discharge cut-off voltage were 2.8-4.3 V. The 0.1C first discharge capacity was 198 mAh / g. The capacity retention rate after 100 cycles at 1C was 78%. Fig.15 .
[0049] from Fig.14 From the distribution of elements, it can be seen that after the multi-stage calcination method in the literature is used to combine a long low-temperature stage with a short high-temperature stage, the concentration gradient trend of the nickel and cobalt elements in the positive electrode material is still slowed down due to the mutual diffusion of metal elements caused by long-term calcination. The multi-stage calcination mode still cannot solve the problem of the slowing trend of the continuous concentration gradient distribution of elements. The nickel content on its surface has also returned to the previous high nickel content component. The highly reactive Ni 4+ It also produces side reactions with the electrolyte solution, causing structural damage to the material, thereby reducing the cycle stability and poor performance.
[0050] The present invention first uses a coprecipitation method to prepare a high nickel ternary precursor with an element concentration gradient structure, and obtains a high nickel ternary positive electrode material with a full concentration gradient structure through a rapid Joule heating process, rapid heating, short-term heat preservation, and rapid cooling. The rapid Joule heating process is controlled, and the concentration gradient distribution of the elements in the high nickel ternary positive electrode material is retained to the greatest extent, inheriting the concentration gradient distribution of the high nickel ternary precursor, inhibiting the uniform diffusion of transition metal ions in the concentration gradient precursor during long-term roasting, and avoiding the problem of disappearance of element concentration gradient caused by traditional furnace roasting. The principle is mainly that the ultra-rapid heating during the rapid Joule heating process causes lithium hydroxide to decompose rapidly into Li2O, and lithium ions quickly diffuse from the surface into the bulk phase, accelerating the generation of the lithiation reaction and the structural phase change of the precursor, and forming a good layered structure in a short time at high temperature. Compared with the traditional long-term furnace calcination, the extremely short heat preservation time makes the transition metal ions inside the precursor particles too late to diffuse, and the ultra-rapid cooling realizes the maintenance of the element concentration gradient. At the same time, the preparation of a high-nickel ternary positive electrode material with high capacity and high cycle stability is also achieved. The preparation process is simple, and the internal concentration gradient trend of the positive electrode material formed by sintering is obvious, which is suitable for industrial production.
[0051] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-nickel ternary positive electrode material for a lithium-ion battery, characterized in that: The method is: Ni with element concentration gradient structure precursor x Co y M 1-x-y (OH)2 and lithium hydroxide are mixed, and the mixed powder is subjected to thermal shock treatment using Joule heat to obtain a high-performance high-nickel ternary positive electrode material containing an element gradient distribution; Ni x Co y M 1-x-y In (OH)2, 0.7≤x<1.0, 0.01≤y<0.1; M is Mn, Al, W, Nb, Mo, Ta or Zr; the concentration of nickel gradually decreases from the core to the particle surface; Lithium hydroxide and Ni x Co y M 1-x-y The total molar ratio of metal ions in (OH)2 is 1.0-1.2:1; The thermal shock treatment is carried out in a pure oxygen atmosphere, with a heating and cooling rate of 373 K / s-773 K / s, a target temperature of 700°C-900°C, and a holding time of 120s-360s.
2. The preparation method according to claim 1, characterized in that: The precursor Ni with element concentration gradient structure x Co y M 1-x-y (OH)2 is prepared in one step by coprecipitation.
3. The preparation method according to claim 1, characterized in that: The method comprises the following steps: spreading the mixed powder on a heated substrate, and applying electricity to the heated substrate in an oxygen atmosphere to achieve thermal shock treatment of the powder.
4. The preparation method according to claim 3, characterized in that: The heating substrates used are carbon cloth, graphite paper, and metal foil.
5. The positive electrode material prepared by the preparation method according to claim 1, characterized in that: The positive electrode material is a high-nickel ternary positive electrode material with an α-NaFeO2 layered structure and belongs to R m space group, the secondary particles of the positive electrode material are spherical, with an average particle size of 6-13 μm and a tap density of 1.8-2.7 g / cm 3 .
6. Use of the positive electrode material as claimed in claim 5 in a lithium-ion power battery.
Citation Information
Patent Citations
Preparation method of high-nickel ternary material with transition metal element concentration gradient and material prepared by preparation method
CN111092221A
Method and device for quickly preparing doped ternary lithium ion battery positive electrode material by using oxygen thermal plasmas
CN112563486A
Preparation method for synthesizing lithium-rich manganese-based positive electrode material by short-time rapid thermal shock method and application of lithium-rich manganese-based positive electrode material
CN113511692A
Preparation method of nano-particles with core-shell structure, nano-particles and application of nano-particles
CN116706011A
Metal gradient dope positive electrode material for lithium ion battery
JP2016139583A
